Collaboration on Rural Clean Water Governance: KPSPAM Institutional Capacity Strengthening and Professionalization Program in South Central Timor Regency - Avessina, Mohammad Jibriel; Bimo, Widhi Ariyo; Firdaus, M. Azis (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
Access to clean water is the foundation of sustainable development and human rights, but its sustainability in rural areas such as South Central Timor (TTS) district faces complex multidimensional challenges. The main problem lies not in infrastructure development alone, but in the weakness of sustainable post-construction support systems. An in-depth political economy analysis shows that these challenges are rooted in chronic local government fiscal constraints, ambiguity in the institutional role between agencies, ceremonial cross-sector coordination, and local political dynamics that often sacrifice the stability of the Drinking Water and Sanitation Supply System Management Group (KPSPAM). The Community Service Program (PKM) is designed as a strategic meeting room to address the root of these governance problems through a participatory and collaborative approach. The method of implementing this program includes a series of structured activities: (1) FGD on participatory problem mapping to build mutual understanding; (2) A continuous mentoring survey for KPSPAM with a focus on managerial, financial, technical, and advocacy aspects to formulate institutional solutions. The results achieved from this program are increased stakeholder awareness of the importance of a paradigm shift from a